Pengaruh Kepuasan Kerja, Motivasi Kerja Dan Komitmen ORganisasi Terhadap Kinerja Karyawan PT Kayu Lima Sentosa Di Magelang - Niken Wulan Sari (JURNAL EKOBIS DEWANTARA, 2018)
ABSTRACT The purpose of this study is to describe (1) the effect of job satisfaction variable on employee performance, (2) influence of work motivation variable to employee performance, (3) influence of organizational commitment variable to employee performance, (4) influence of job satisfaction variable, work motivation and organizational commitment together to the performance of employees of PT. Wood Five Sentosa In Magelang. The nature of research in this study is quantitative. The research variables studied were job satisfaction (X1), work motivation (X2), organizational commitment (X3), and employee performance (Y). Its population is employees of PT. Sentosa Five Woods In Magelang, totaling 125 employees. The sample was 95 employees using slovin formula. The sampling technique was done by accidental sampling method. Data collecting method using kuisoner, while data analysis technique using multiple linear regression analysis supported by F test and T test and classical assumption test consist of multikolineritas test, normality test, and heteroscedasticity test. The results showed that the linear regression equation for the three predictors was Y = 0.199 + 0.383X1 + 0.252X2 + 0.418X3. That is, job satisfaction (X1) has a significant positive effect on employee performance (Y) with significance level 0,000 <α 0.05. Work motivation (X2) has a significant positive effect on employee performance (Y) with significance level 0,000 <α 0,05. Organizational commitment (X3) has a significant positive effect on employee performance (Y) with a significance level of 0,000 <α 0.05. Together variables Job Satisfaction (X1), Work Motivation (X2), and Organizational Commitment (X3), have a significant positive effect on Employee Performance (Y) at PT. Wood Five Sentosa In Magelang with a significance of 0,000<α 0.05. Keywords: job satisfaction, work motivation, organizational commitment and employee performance.